2010
DOI: 10.1111/j.1600-0501.2009.01908.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of six different peri‐implantitis disinfection methods on in vivo human oral biofilm

Abstract: All tested antiseptics seem to be able to reduce the total amount of microorganisms accumulating on titanium surfaces. Furthermore, sodium hypochlorite, hydrogen peroxide, chlorhexidine, and Listerine showed a significant bactericidal effect against adhering bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
2
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(141 citation statements)
references
References 59 publications
(133 reference statements)
5
127
2
7
Order By: Relevance
“…For the treatment of peri-implant diseases, oral hygiene instructions should be undertaken in order to enhance oral hygiene of natural teeth and dental implants. 40 Unfortunately, studies on treatment options for peri-implant diseases are generally limited in number, with small sample sizes and short follow up periods. 41 However, clinical data must be interpreted from controlled and randomized studies, with big sample size.…”
Section: Discussionmentioning
confidence: 99%
“…For the treatment of peri-implant diseases, oral hygiene instructions should be undertaken in order to enhance oral hygiene of natural teeth and dental implants. 40 Unfortunately, studies on treatment options for peri-implant diseases are generally limited in number, with small sample sizes and short follow up periods. 41 However, clinical data must be interpreted from controlled and randomized studies, with big sample size.…”
Section: Discussionmentioning
confidence: 99%
“…So far, this variable has not been evaluated, with studies found in which the volunteers did not brush their teeth at all [50,51], while there are others in which they did [79,52,53]. Our results revealed that the thickness of the SF-biofilm formed after 48 h and its bacterial viability were significantly affected by the toothbrushing protocol, as these microscopic parameters were higher in test 1 (without toothbrushing), especially in the medial-mesial positions.…”
Section: Discussionmentioning
confidence: 99%
“…Using this model, we have generated realistic biofilms on dental implants in 48 h and then used these to test the effectiveness of various debridement methods. Other groups have likewise developed methods for developing dental plaque on implants using in situ appliances [102][103][104], and this will likely be a productive approach for future studies. A particular advantage of our own system is that it can use both a flat titanium disc and an actual commercial titanium implant, whereas other models use flat titanium discs.…”
Section: In Situ Modelsmentioning
confidence: 99%